2021
DOI: 10.1111/anae.15511
|View full text |Cite
|
Sign up to set email alerts
|

Fire safety and emergency evacuation guidelines for intensive care units and operating theatres: for use in the event of fire, flood, power cut, oxygen supply failure, noxious gas, structural collapse or other critical incidents

Abstract: Summary The need to evacuate an ICU or operating theatre complex during a fire or other emergency is a rare event but one potentially fraught with difficulty: Not only is there a risk that patients may come to harm but also that staff may be injured and unable to work. Designing newly‐built or refurbished ICUs and operating theatre suites is an opportunity to incorporate mandatory fire safety features and improve the management and outcomes of such emergencies: These include well‐marked manual fire call points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…As described in other studies, training, practical exercises, and simulation training enhance the disaster response [41][42][43] . Most of the respondents in this study con rmed the invaluable impacts of disaster simulation rehearsal, including re evacuation, at least once a year.…”
Section: Staff and Stuffmentioning
confidence: 69%
“…As described in other studies, training, practical exercises, and simulation training enhance the disaster response [41][42][43] . Most of the respondents in this study con rmed the invaluable impacts of disaster simulation rehearsal, including re evacuation, at least once a year.…”
Section: Staff and Stuffmentioning
confidence: 69%
“…In summary, the findings of this study accentuated the shortcomings of hospital evacuation preparedness in terms of comprehensive surge planning including staff, stuff, and structure capacities and capabilities to create effective systems, seamless multiagency collaboration, and opportunities for community engagement. Previous studies have demonstrated the value of realistic and practical exercises and training in improving disaster responses (Sammut et al 2001 ; Berlin and Carlström 2015 ; Khorram-Manesh et al 2015 ; Kelly et al 2021 ). Moreover, they facilitate the identification of contingency plan gaps and potential technical and strategic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Similar systems can be used to remove anaesthetic gases from hospital effluent, and working systems have already been installed in some hospitals [5]. Alternative approaches are also available; if retrofitting a hospital's waste gas scavenging system is not practical, the anaesthetic gas can be captured using canisters of activated carbon and recovered at a central facility.…”
mentioning
confidence: 99%